What are the antecedents of women’s entrepreneurial orientation? - Santos, Gina (2018)
This study seeks to identify the antecedents of women’s entrepreneurial orientation (EO) and exploring what possible relationships that may exist between them. The research focuses on women entrepreneurs and non-entrepreneurs in a quantitative perspective whose methodology consisted of the collection of primary data through a survey distributed to women in Portugal. After structural equation modelling was applied, the results suggested that recognition of opportunities influences EO. This influence is expressed both directly and indirectly through training in management and entrepreneurial skills. These findings led to the conclusion that policies promoting training for community members, in general, need to be rethought and policies need to emphasise training in management that enhances entrepreneurial skills, thereby increasing the proliferation of entrepreneurship. Entrepreneurship education and training should be promoted from basic education onwards in order to develop entrepreneurial skills from an early age. Prior to this study, the relationships between opportunity recognition, management training and entrepreneurial skills have never been studied in relation to women.